The effect of biochar and liquid organic fertilizer to Mentha spicata physiological activities - Rahayu Muji; Rahmawan Bayutama; Sakya Amalia Tetrani; Setyawati Andriyana; Handoyo Gani Cahyo; Anggraini Rissa Kurnia (BIO Web of Conferences)
Mint (Mentha spicata L.) is a medicinal plant that produces essential oils usually used in medicines, food, toothpaste, and cosmetics. Mint leaves are the primary organ taken as an essential oil production material. Increasing leaf production, which is studied through the physiological activity of mint, can be done by meeting plant nutrient needs. Biochar and liquid organic fertilizer (LOF) can be used as alternative soil conditioners and fertilizers to meet plant nutrient needs. This research was conducted in the Faculty of Agriculture’s Greenhouse using a factorial Randomized Complete Group Design (RCGD), which consists of two factors, namely biochar and liquid organic fertilizer of fish waste. The type of biochar consists of no biochar treatment, palm fiber biochar, and rice husk biochar. Fish waste liquid organic fertilizer consists of no LOF treatment, 5 ml/L water, 10 ml/L water, and P3 15 ml/L water. The results of biochar types increased the chlorophyll content of mint, which were 1.14, 0.51, and 1.14 mg.g-1. The treatment of fish waste liquid organic fertilizer increased the transpiration rate of mint, which were 1.27 CO2-1.L-1.minute-1.